68.5k views
2 votes
2(x + 1 ) - 3(x + 5) ≥ 0
plss help

2 Answers

6 votes

Answer:

x ≤ -13

Explanation:

2(x + 1) - 3(x + 5) ≥ 0

Distribute the 2

(2 × x) + (2 × 1)

2x + 2 - 3(x + 5) ≥ 0

Distribute the -3

(-3 × x) + (-3 × 5)

2x + 2 - 3x + (-15) ≥ 0

2x + 2 - 3x - 15 ≥ 0

Combine like terms

2x - 3x + 2 - 15 ≥ 0

-x + (-13) ≥ 0

-x - 13 ≥ 0

+13 +13

-x ≥ 13

Divide both sides by -1 and flip the sign

x ≤ -13

User Zeeshan Ayaz
by
4.5k points
2 votes

Answer:

Inequality form x less than or equal to -13

Step-by-step explanation

User Demonedge
by
5.2k points